2013
DOI: 10.2466/03.09.pr0.112.2.445-457
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Psychopathy Checklist–Revised and the MMPI–2: A Pilot Study

Abstract: The goal of the study was to investigate the relationship between Hare's four-facet model of psychopathy and the Minnesota Multiphasic Personality Inventory-2 (MMPI-2) in a forensic, culturally homogenous sample. 22 male prisoners from Bergen Prison participated. There was only a statistically significant negative zero-order correlation between the total PCL-R score and the score on the Depression scale of the MMPI-2. However, the results revealed that the four facets had different underlying correlates with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
1
7
0
1
Order By: Relevance
“…Additionally, these findings are consistent with previous studies showing that affective aspects of psychopathy were related to some forms of adaptive behavior such as low anxiety/distress and emotional stability (e.g. Fanti et al, 2016;Hansen et al, 2013;Sica et al, 2015). One possible explanation is that callous and emotional detachment traits of psychopathy lead to higher levels of hardiness, which refers to a set of personality characteristics that appear to protect individuals from the negative physical and mental health effects of stress (Kobasa, 1979), and was found to be a partial mediator of the relationship between psychopathy and anxiety (Sandvik et al, 2015).…”
Section: Affective Psychopathy Traits and Emotional Distresssupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, these findings are consistent with previous studies showing that affective aspects of psychopathy were related to some forms of adaptive behavior such as low anxiety/distress and emotional stability (e.g. Fanti et al, 2016;Hansen et al, 2013;Sica et al, 2015). One possible explanation is that callous and emotional detachment traits of psychopathy lead to higher levels of hardiness, which refers to a set of personality characteristics that appear to protect individuals from the negative physical and mental health effects of stress (Kobasa, 1979), and was found to be a partial mediator of the relationship between psychopathy and anxiety (Sandvik et al, 2015).…”
Section: Affective Psychopathy Traits and Emotional Distresssupporting
confidence: 92%
“…Psychopathy represents a complex construct involving distinguishable features in the domains of affect (e.g., lack of empathy/remorse, callousness, fearlessness, Blackburn (1975Blackburn ( , 1979 hypothesized that the anxiety is the key phenotypic distinction between the two psychopathy types, with primary psychopathy being characterized by low anxiety and social dominance, and secondary by high anxiety and social withdrawal. Indeed, previous studies found a negative association between Factor 1 and trait anxiety, and/or a positive relation between Factor 2 and anxiety (Hansen, Stokkeland, Pallesen, Johnsen, & Waage, 2013;Harpour, Hare, & Hakstian, 1989;Hicks, Markon, Patrick, Krueger, & Newman, 2004;Hicks & Patrick, 2006;Sandvik, Hansen, Hystad, Johnsen, & Bartone, 2015). Moreover, the importance of distinction between Factor 1 traits and Factor 2 psychopathy characteristics can be observed in their relations with several forms of psychopathology.…”
Section: Introductionmentioning
confidence: 93%
“…Prior research has found a negative association between anxiety and the interpersonal and affective facets (Hansen et al, 2013; Neumann & Pardini, 2014). However, evidence from prisoner samples have not found a significant association between psychopathy and anxiety (Hale et al, 2004; Sandvik et al, 2015; Schmitt & Newman, 1999).…”
Section: Discussionmentioning
confidence: 96%
“…A meta-analysis of 102 studies using the 2-factor model of psychopathy found that anxiety was negatively related to factor 1 (interpersonal and affective facets), and factor 2 (lifestyle and antisocial facets) was positively associated with anxiety (Derefinko, 2015). Research testing the 4-facet model in a small prisoner sample ( N = 22) found only the interpersonal facet was negatively related to anxiety (Hansen et al, 2013). Neumann and Pardini (2014) found higher levels of internalizing symptoms (e.g., anxiety, depression) were negatively related to affective facet scores and positively related to the lifestyle facet.…”
Section: Introductionmentioning
confidence: 99%
“…Varios autores 8,9 hicieron referencia a las tres estructuras de la corteza prefrontal CPF con funcionalidad diferente: a) corteza ventrolateral (CPFVL), que se asocia con procesos de mantenimiento de la información; b) corteza dorsolateral (CPFDL) relacionada con procesos de manipulación y verificación de la información; c) corteza anterior que está vinculada con la selección de objetivos 10 . Las lesiones en la CPF no suele conllevar una pérdida generalizada de la memoria sino con las estrategias mediadoras 11,12 , lo cual guarda relación con el sistema y enfoque de organización funcional cerebral ya reportado por Luria y otros autores, identificando tres sistemas (unidades) funcionales: primer sistema funcional, bloque de activación-motivación-excitación; segundo sistema funcional; bloque input: recibir, procesar y almacenar información; y tercer sistema funcional, bloque de programación, encargado de la programación, control y verificación de la actividad 13,14 .…”
Section: Introductionunclassified